Analysis of Factors Affecting Teacher Performance ( Case Study at State Senior High School 12 Medan) - Theresia Sinaga; Yohni Anwar; M. Chaerul Rizky (International Journal of Management, Economic and Accounting, 2025)
Study This aiming For analyze factors that influence teacher performance at SMA Negeri 12 Medan. Research This use approach quantitative with type study descriptive causal . Population in study This is all teachers of State Senior High School 12 Medan who have own certificate educator as many as 49 people. Retrieval technique sample using saturated sampling Where all over population made into as sample research . The data used consists of from the primary data obtained through distribution questionnaire to respondents , and secondary data obtained from documentation school . Data collection was carried out through method questionnaires , observations , and studies documentation . Data analysis techniques using analysis multiple linear regression with SPSS software version 29 assistance . Before done analysis regression , data first formerly tested with assumption test classical tests including normality tests , multicollinearity tests , and heteroscedasticity tests . The results of the study show that in a way partial variable Discipline Work , Competence , and Motivation Work influential positive and significant to teacher performance . On the other hand , the allowance Profession No influential significant to teacher performance . The results of the simultaneous F test also confirmed that fourth variable in a way together influential positive and significant to teacher performance . Regression model show The R value is 0.718, which indicates connection positive enough strong between variable independence and teacher performance .